EVALUASI KINERJA STRUKTUR BANGUNGAN BERTINGKAT 4 LANTAI KAMPUS AKADEMI KOMUNITAS NEGERI (AKN) PUTRA SANG FAJAR BLITAR DENGAN METODE ANALISIS RESPON SPEKTRUM MENGGUNAKAN APLIKASI STAAD PRO - nurjanah; Rozaqi, bahar (Universitas Islam Balitar Blitar, 2023)
Campus Akademi Komunitas Negeri (AKN) Putra Sang Fajar Blitar located on sub-district Sananwetan, Blitar City, this integrated lecture building stands on the land of the former Mardiwaluyo Hospital. The campus building has a total of 4 floors that function as an educational building. The calculation method uses the STAAD Pro progam to determine the results of the analysis of the performance of the building’s structure starting from beams, columns, sloof to foundations. after the calculation results in a floor slab with a thickness of 12 cm using a 2-way plate system, with K-300 (Fc’) = 24,9 Mpa and steel quality (fy) = 400 Mpa. While the beam is 60 cm x 40 cm, 50 cm x 30 cm, 40 cm x 30 cm, 30 cm x 20 cm with quality concrete K-300 (Fc’) = 24,9. Column size 40 cm x 40 cm and sloof size 60 cm x 30 cm dan 50 cm x 25 cm with quality concrete K-300 (Fc’) = 24,9 lower structure using footplat foundation. From the dimensions above, it is estimated that this reanalysis calculation is more efficient and can reduce project costs.